Alimentación ninfal de Leptophlebiidae (Insecta: Ephemeroptera) en el Caño Paso del Diablo, Venezuela - Bello C, Carlos Luis; Cabrera F., María Isabel (Revista de Biología Tropical, 2001)
The food habits of aquatic nymphs of 12 species of the family Leptophlebiidae were determined in a tropical intermittent stream in Venezuela . Three monthly samples of aquatic insects were taken from January to June in 1989. Two hundred and twenty-five stomach contents were analyzed. The results obtained were compared by the functional feeding groups classification. Species of the Thraulodes and Farrodes genera show significant differences in their diets